PEMAHAMAN KEAGAMAAN UMAT DAN RELEVANSINYA TERHADAP PLURALISME AGAMA PADA MASYARAKAT KOTA TANGERANG - Karmawan, Karmawan (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This study aims to find the religious understanding of the people and their levance to religious pluralism in the people of the city of Tangerang. The results show that the people of Tangerang City appreciate and accept both religious pluralism and pluralism in society, and support the creation of inter-religious harmony. This condition was encouraged by the significant role of the Tangerang City government, and the office of the Ministry of Religion of the City of Tangerang which gave serious attention to improving and fostering inter-religious harmony. The role of institutions and religious leaders as well as community pillars becomes strong in strengthening and realizing inter-religious harmony. With the role of these related parties, making Tangerang City a harmonious city with various religions and cultures.